Antibacterial and antifungal activity of essential oils - Habib, Tasnim Ibnat; Meena, Shivani; Ranote, Priyanka; Karnani, Tamanna; Chauhan, Uday Veer Singh; Kumar , Arvind (Journal of Postharvest Technology, 2021)
The antimicrobial properties of essential oils are extremely significant. Essential oils are useful as an organic medicine for a variety of diseases also they are used in a variety of industries. From various research studies, this analysis shows some essential oils and their use against harmful bacteria. The researchers have devoted much focus to the study of natural antimicrobial compounds in medicine. This is mostly because of antimicrobial-resistant pathogens. Essential oils are volatile, natural, complex, strong odor compounds, which are formed as secondary metabolites by aromatic plants. They have been extensively used in applications including bactericidal, virucidal, fungicidal, antiparasitic, insecticidal, health, and antioxidants. The mechanism of action of essential oils makes them unique to be used against various pathogens. Many essential oils are study for their antifungal activities. Citronella, geranium, lemongrass, peppermint among others have been examined distinctively against fungi and found to be helpful antimicrobials for that purpose. In this review article, we will provide a summary of essential oils used against various pathogens, their mode of action, and future perspective for the use of essential oils as a potential antimicrobial. Essential oils